Preferensi Belanja Mahasiswa di Kabupaten Jember Melalui Platform Marketplace - Ningrum, Nurita Kustiari (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The development of information technology has significantly changed consumer behavior patterns, especially when it comes to shopping. The phenomenon of shopping through marketplaces is increasingly becoming a dominant trend among students in Jember Regency. The district, known for its large student population, is an interesting subject to study regarding the factors that influence shopping interest through these e-commerce platforms. In this study, the researcher applied a quantitative approach and data collection was carried out through the application of questionnaires using the Likert scale. The population in this study is PTN students in Jember district, which is 78,839 students consisting of 9989 students of the Jember State Polytechnic, 53,120 students of the University of Jember, and 15,730 students from UIN Khas Jember.